rTMS combined with median nerve magnetic stimulation for prolonged disorders of consciousness following intracerebral hemorrhage: a randomized controlled trial protocol - Chen, Hanbo; Chen, Si; Wen, Weifeng; Guo, Yongliang; Luo, Yong; Li, Junfu; Huang, Shujuan; Lv, Xiao (Frontiers in Neurology, 2025)
BackgroundProlonged disorders of consciousness (pDoC) following intracerebral hemorrhage significantly impact patient quality of life, with limited effective standardized treatments available. While repetitive transcranial magnetic stimulation (rTMS) and median nerve stimulation show individual therapeutic potential, high-quality clinical evidence for combined treatment protocols remains lacking.MethodsThis randomized controlled trial will enroll 129 patients with pDoC following intracerebral hemorrhage, randomly allocated to three groups: combined group (median nerve magnetic stimulation (MNMS) followed by rTMS treatment), rTMS group (sham MNMS followed by rTMS treatment), MNMS group (MNMS followed by sham rTMS treatment). The primary outcome is the Coma Recovery Scale-Revised (CRS-R) score at 3 weeks post-treatment. Secondary outcomes include Glasgow Coma Scale scores, brainstem auditory evoked potentials, somatosensory evoked potentials, and safety assessments. Statistical analysis will employ repeated measures ANOVA and appropriate post-hoc tests.DiscussionThe combined treatment mechanism is based on multilevel consciousness network modulation theory, integrating “top-down” cortical regulation through rTMS and “bottom-up” sensory pathway activation through median nerve magnetic stimulation. This bidirectional approach may achieve more comprehensive consciousness network repair compared to single modalities. The study’s rigorous three-group design and comprehensive assessment combining clinical scales with electrophysiological indicators will provide robust evidence for the clinical application of neuromodulation techniques in consciousness disorders.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=256274, identifier ChiCTR2500106064.